P128 Double-blind randomized pilot study to evaluate diamagnetically enhanced transdermal ibuprofen in comparison to placebo on pain and function in individuals with knee osteoarthritis. (23rd April 2022) - Summers, Jill; Wright, Tony; Benson, Heather; Moss, Penny; Tsadilas, George; Edwards, Jeff; Will, Rob
Abstract: Background/Aims: Treatment of knee osteoarthritis (OA) focuses on reducing pain and improving function. Transdermal NSAID formulations have been developed as an alternative approach to reduce pain and sensitisation around the OA affected joint whilst avoiding some of the risks associated with oral NSAID administration. The aim of the study was to evaluate clinical outcomes following short-term (48 hours) administration of transdermal ibuprofen (5% w/v) from a wearable patch that incorporated a patented diamagnetic repulsion technology to enhance drug delivery, in comparison to placebo. Methods: Double-blind, repeated measures, crossover design. Two study periods (48 hr each); diamagnetically enhanced ibuprofen or placebo, randomised. Participants: 24 (6 male: 18 female, mean age 66) people with painful knee OA. Patch applications: 6 x 4-5 hour patch applications over a 48 hour period. Active patches contained 5% ibuprofen in a gel reservoir with magnetized backing. Placebo patches had identical appearance but no ibuprofen and non-magnetized backing. Primary outcome measures: VAS for pain on movement (STS X3), WOMAC pain score, WOMAC function score. Results: Conclusion: The active device containing ibuprofen (5%) and magnetophoresis technology produced a significantly greater reduction in pain and improvement in function than the placebo device. This was particularly the case for movement related pain. The reduction in pain was apparent with both VAS pain ratings and WOMAC pain score. There was also a clear improvement in function based on the WOMAC function score. The number needed to treat (NNT) for a 50% reduction in movement related pain was 2.2 and for resting pain 3.4. There were no major adverse events recorded during the study. Disclosure: J. Summers: None. T. Wright: None. H. Benson: None. P. Moss: None. G. Tsadilas: None. J. Edwards: None. R. Will: None.